2017
DOI: 10.1515/pjmpe-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

Neutron and photon scattering properties of high density concretes used in radiation therapy facilities: A Monte Carlo study

Abstract: In the current study the neutron and photon scattering properties of some newly developed high density concretes (HDCs) were calculated by using MCNPX Monte Carlo code. Five high-density concretes including Steel-Magnetite, Barite, Datolite-Galena, Ilmenite-ilmenite, Magnetite-Lead with the densities ranging from 5.11 g/cm 3 and ordinary concrete with density of 2.3 g/cm 3 were studied in our simulations. The photon beam spectra of 4 and 18 MV fromVarian linac and neutron spectra of clinical 18 MeV photon beam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…There are studies on the use of high-density concrete for radiotherapy rooms as substitutes for lead and steel plates. These studies [22][23][24][25] analyze analytical capture models for installation design, which are conservative estimators for capture calculations, successfully verifying their feasibility.…”
Section: Introductionmentioning
confidence: 88%
“…There are studies on the use of high-density concrete for radiotherapy rooms as substitutes for lead and steel plates. These studies [22][23][24][25] analyze analytical capture models for installation design, which are conservative estimators for capture calculations, successfully verifying their feasibility.…”
Section: Introductionmentioning
confidence: 88%
“…21 Furthermore, it has been reported that the scattering intensities of photons and neutrons vary depending on the composition of the HDC. 22 In the current study, the addition of two high-density NPs including Osmium (Os, Z = 76) and Iridium (Ir, Z = 77) to the ordinary concrete was considered. Osmium is the densest element in nature with a density of 22.59 g/cm 3 .…”
Section: Introductionmentioning
confidence: 99%